PENERAPAN METODE GAMIFIED LEARNING BERBASIS MEDIA PLATFORM EDUCAPLAY UNTUK MENINGKATKAN KEAKTIFAN BELAJAR PADA SISWA KELAS V SDN DUPAK 1 SURABAYA - Putri Atika; Roni Rodiyana; Dwi Natalia (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This research was motivated by the lack of active learning among class V students at SDN Dupak 1 Surabaya. This happens because teachers are still too monotonous in applying learning methods and media. The aim of this research is to increase student learning activity in the classroom learning process through the application of a gamified learning method based on the interactive educational game Educaplay. This research uses the Classroom Action Research method in two cycles. Each cycle is carried out with four stages of activity, namely planning, action, observation and reflection. The subjects in this research were class V students at SDN Dupak 1 Surabaya with a total of 30 students. The results of the pre-cycle research showed that the average result of student activity was 34.9%, while in cycle I the percentage was 56.7% and increased by 80.7% in cycle II. Thus, it can be concluded that the use of gamified learning methods based on the Educaplay media platform can increase the learning activity of class V students at SDN Dupak 1 Surabaya.